General and Academic Vocabulary Sizes and Reading Comprehension among the First Year BSED English Students - Cawagdan-Cuarto, Harieth; Cuenca, Pia; Gonito, Judy-Ann; Lyka Maan, Kalaw (JPAIR Institutional Research, 2023)
Proficiency in the English language comprises a wide range of skills, including listening, speaking, reading, and writing. Among these skills, reading comprehension holds particular importance as it enables students to effectively process and understand written text. An essential factor contributing to successful reading comprehension is vocabulary, which plays a fundamental role in the reading process. This study aimed to explore the relationship between reading comprehension and vocabulary, specifically focusing on general and academic vocabulary commonly used in English learning and academic settings. The research utilized a descriptive-correlational method, employing Pearson’s r method to establish a significant relationship between the two variables. The results revealed significant findings for each type of vocabulary and reading comprehension. The learners demonstrated a very high general vocabulary and an above-average academic vocabulary size. Additionally, the learners exhibited an average level of reading comprehension. These statistical findings emphasize the significant relationship between the variables studied, emphasizing their mutual influence. To enhance students’ academic performance, the researchers suggest implementing modules comprising diverse activities and exercises to promote the development of both academic vocabulary and reading comprehension skills.